2010
DOI: 10.1080/01690965.2010.490047
|View full text |Cite
|
Sign up to set email alerts
|

Auditory sensitivity to formant ratios: Toward an account of vowel normalisation

Abstract: A long-standing question in speech perception research is how do listeners extract linguistic content from a highly variable acoustic input. In the domain of vowel perception, formant ratios, or the calculation of relative bark differences between vowel formants, have been a sporadically proposed solution. We propose a novel formant ratio algorithm in which the first (F1) and second (F2) formants are compared against the third formant (F3). Results from two magnetoencephelographic (MEG) experiments are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 88 publications
3
37
3
1
Order By: Relevance
“…Additionally, it has also been suggested that N1 might be sensitive to the F 1 /F 3 ratio instead of absolute formant values (Monahan & Idsardi, 2010). Similar to the rationale in the current paper, that proposal was made in the light of a mechanism that helps listeners deal with between-speaker variation in formant frequencies, but then in a vowel-intrinsic manner (i.e., relying only on information within the target vowel).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Additionally, it has also been suggested that N1 might be sensitive to the F 1 /F 3 ratio instead of absolute formant values (Monahan & Idsardi, 2010). Similar to the rationale in the current paper, that proposal was made in the light of a mechanism that helps listeners deal with between-speaker variation in formant frequencies, but then in a vowel-intrinsic manner (i.e., relying only on information within the target vowel).…”
Section: Discussionsupporting
confidence: 49%
“…Similar to the rationale in the current paper, that proposal was made in the light of a mechanism that helps listeners deal with between-speaker variation in formant frequencies, but then in a vowel-intrinsic manner (i.e., relying only on information within the target vowel). In contrast to Monahan and Idsardi (2010) and the other papers mentioned above, the current paper focused on vowel-extrinsic influences on perception, as the set of target vowels were identical across the two context conditions. In speech perception, vowel intrinsic normalization and normalization for vowel-extrinsic acoustic information probably operate in tandem (Johnson, 2005), and extrinsic normalization procedures have the potential to play a large role in overcoming betweenspeaker variation that is the result of anatomical/physiological differences between speakers .…”
Section: Discussionmentioning
confidence: 99%
“…The latency and amplitude of the M100 has been shown to correlate with the fundamental frequency of tones (Roberts & Poeppel, 1996; Woods, Alain, Covarrubias, & Zaidel, 1995) and the first formant frequency of vowels (Poeppel & Marantz, 2000; Roberts, et al, 1998). Recent work suggests an additional sensitivity to vowel formants ratios in dense vowel spaces (Monahan & Idsardi, 2010). Larger ratios between the first and third vowel formant (F1/F3) elicited earlier M100 latencies.…”
Section: Testing Features In the Brainmentioning
confidence: 99%
“…• l'échelle des equivalent rectangular bandwidth-rate (ou ERB-rate), proposée par Peterson, 1951;Monahan et Idsardi, 2010). Comme l'illustre la Figure On peut également calculer la distance, sur une échelle tonotopique, telle que celle des barks, entre deux formants ou entre un formant et la Fo.…”
Section: Normalisation Vocaliqueunclassified